Perbandingan efektivitas pupuk kandang sapi dan pupuk urea terhadap pertumbuhan vegetatif tanaman jagung (Zea mays L.) - Ramadhani, Syifa Zalina; Zafit, Vernika; Syamsurizal, Syamsurizal (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Corn (Zea mays L.) is an important commodity as a source of carbohydrates in Indonesia, so proper fertilization is needed to increase its productivity. This study aims to determine the comparison of the effectiveness of cow manure and urea fertilizer on the growth of corn plants. The method used is an experiment with a Completely Randomized Design (CRD). The parameters measured include plant height and number of leaves. Based on the results of the study, the application of cow manure gave significant results on plant height and number of leaves of corn plants compared to urea fertilizer. The treatment of giving cow manure with a dose of 12 g/plant had better plant height and number of leaves compared to other treatments. The conclusion of this study is that the application of cow manure has a significant effect on plant growth and has the potential to be more effective in increasing the vegetative growth of corn plants.